(3JGQjN eOjfI GUHgGfs - (3CMeO Hf YHO Gddg Hf CMeO GdCUHgGfj, CHh fYje, J (B430 (3g` s
(3ChdgG (B:s
(3CNHQfG jhSa Hf Ndjd Hf YHO Gddg GdOeTbi CNHQfG CHh Ydi GdMSf Hf CMeO GdMOGO , bGd GdTjN CHh fYje GdMeO ddg QH GdYGdejf heHOY GdSeGhGJ hGdCQVjf s
(3BNQgG (B:s
(3ef JQLeI djd HfJ CMeO Hf eSde GdOjfi (B: (3hef ONd ai gPG GdOjf agh YQHi s
(3QhGjI CHj Ydi GdMSf Hf CMeO Hf GdMSf GdMOGO GdebQi HBNQgG SeGY JGQjNg SfI (B591 (3hSeGY BNQ SfI (B638s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3JGQjN (B49) s
Keywords: (3GdJGQjNs